AutoMorph: Accelerating morphometrics with automated 2D and 3D image processing and shape extraction. Issue 3 (9th November 2017) - Hsiang, Allison Y.; Nelson, Kaylea; Elder, Leanne E.; Sibert, Elizabeth C.; Kahanamoku, Sara S.; Burke, Janet E.; Kelly, Abigail; Liu, Yusu; Hull, Pincelli M.
Abstract: Large‐scale, comparative studies of morphological variation are rare due to the time‐intensive nature of shape quantification. This data gap is important to address, as intraspecific and interspecific morphological variation underpins and reflects ecological and evolutionary processes. Here, we detail a novel software package, AutoMorph, for high‐throughput object and shape extraction. AutoMorph can batch image many types of organisms (e.g. foraminifera, molluscs and fish teeth), allowing for rapid generation of assemblage‐scale morphological data. We used AutoMorph to image and generate 2D and 3D morphological data for >100, 000 marine microfossils in about a year. Our collaborators have used AutoMorph to process >12, 000 patellogastropod shells and >50, 000 fish teeth. AutoMorph allows users to rapidly produce large amounts of morphological data, facilitating community‐scale evolutionary and ecological studies. To hasten the adoption of automated approaches, we have made AutoMorph freely available and open source. AutoMorph runs on all UNIX‐like systems; future versions will run across all platforms.